IMPROVING METHODS FOR DEVELOPING LEARNING ACTIVITIES IN FUTURE PRIMARY CLASS TEACHERS (TAMADDUN NURI JURNALI, 2024)
In this article, the essence of the topic of improving the methodological training of future primary school teachers for the intellectual development of students and the content of the concept of methodological training, the factors necessary for a teacher to develop methodological literacy and the necessary pedagogical conditions and necessary resources are studied theoretically.